Using Digital Visual Literacy to Improve Reading Skills of Junior High School Students in Remote Islands - Tiwery, Dian Sartin (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2025)
This Classroom Action Research investigated the use of Digital Visual Literacy (DVL) to improve the reading comprehension of Grade VIII students at SMP Negeri 2 Tiakur, a junior high school located in the remote islands of Maluku Barat Daya. The study was conducted in two cycles following the Kemmis and McTaggart model, involving 23 students and employing multi modal materials such as images, infographics, videos, PowerPoint slides, and digital stories. Data were collected through pretest and post-tests, observation checklists, questionnaires, and interviews. The findings revealed significant improvement in students’ reading comprehension, with mean scores increasing from 56.2 in the pretest to 67.8 in Cycle 1 and 79.1 in Cycle 2. Students showed better ability to identify main ideas, infer information, and understand vocabulary in context. Qualitative results also indicated increased engagement, collaboration, and motivation during reading activities, supported by students’ positive perceptions of DVD-based learning. Despite limited technological infrastructure, the integration of offline digital and visual materials proved feasible and effective in the remote island context. Overall, the study concludes that Digital Visual Literacy enhances both cognitive and affective aspects of reading, making it a powerful instructional approach for improving literacy outcomes in EFL classrooms, particularly in undeserved and low-resource regions.